2020
DOI: 10.1080/2574254x.2020.1769992
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among under-five children in South Asia

Abstract: In parallel with high prevalence of undernutrition, the low-middle-income countries like those in South Asia are experiencing an increasing burden of overweight and obesity among under-five children. The present study aims to measure the prevalence of overweight and obesity and their sociodemographic correlates among under-five children in selected South Asian countries. Methods: Cross-sectional data on 132,231 mother-child pairs were extracted from Demographic and Health Surveys conducted in Bangladesh (2014)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
4
10
1
Order By: Relevance
“…[ 23 ] Further Research also shows that on rising the burden of obesity among the Asian population found overweight prevalence and obesity was only 22% higher among the high socioeconomic class community. [ 24 25 ] Significant association was found with non-vegetarian dietary habits and adolescent obesity, adolescent who were using chocolate showed a significant association with overweight/obesity which are new association we found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…[ 23 ] Further Research also shows that on rising the burden of obesity among the Asian population found overweight prevalence and obesity was only 22% higher among the high socioeconomic class community. [ 24 25 ] Significant association was found with non-vegetarian dietary habits and adolescent obesity, adolescent who were using chocolate showed a significant association with overweight/obesity which are new association we found in this study.…”
Section: Discussionsupporting
confidence: 76%
“…This study revealed that the pooled prevalence of overweight and/or obesity among under-five children in East Africa was 4.59 % (95% CI ¼ 4.45-4.73). This finding is higher than a study conducted in Maldives and Nepal [20]. While the finding of this study is lower than studies conducted in Ethiopia [14,21,22], Cameron (8%) [23], and sub-Saharan Africa (6.8%) [24].…”
Section: Discussioncontrasting
confidence: 81%
“…Under-five children born from rich households had a one-fourth risk of overweight and/or obesity as compared to children born from poor household wealth. Similarly, previous studies in Ethiopia [14], South Asia [20], sub-Saharan Africa [32], and Guangzhou, China [33] reported that children born from rich households were at high risk of overweight and/or obesity. In contrast to this, another study in sub-Saharan Africa evidenced that household wealth status had no significant effect on under-five obesity [24].…”
Section: Discussionmentioning
confidence: 54%
“…These were similar results to our study; however, Martinson et al [31] used a different BMI reference. A recent study reported a very low prevalence of overweight (1.91%) and obesity (.89%) in children from South Asia under 5 years of age [32].…”
Section: Discussionmentioning
confidence: 95%